Dziecko z zaburzeniami mowy w systemie oświaty - Olempska-Wysocka, Magdalena (Wydawnictwo Naukowe UAM, 2014)
The article presents considerations for children's speech and communication disorders. Polish and foreign literature can be considered to present variety of terms and definitions, however not clear in meaning. It can be found creating difficulties not only in terms of diagnostic but as well as in therapeutic process. Article emphasizes important issues of speech disorder children in education process, care, special education forms complaint with law. Issues related to psycho-social speech disorder was also raised in this article.
Children with a Speech Impairment in the School System
Keywords: aphasia; developmental aphasia; dysphasia; speech disorders; specific language impairment (SLI); special educational needs; psychological and pedagogical assistance